2020
DOI: 10.2196/19914
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Rehabilitation of Patients With Musculoskeletal Diseases of the Shoulder: Scoping Review

Abstract: Background Gamification has become increasingly important both in research and in practice. Particularly in long-term care processes, such as rehabilitation, playful concepts are gaining in importance to increase motivation and adherence. In addition to neurological diseases, this also affects the treatment of patients with musculoskeletal diseases such as shoulder disorders. Although it would be important to assist patients during more than one rehabilitation phase, it is hypothesized that existin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Randomized controlled trials delivering physical therapy care by telerehabilitation were included. The experimental group received telerehabilitation, which was considered as home-based exercises delivered through mobile applications, web-based instruments, exergames, 24 and videoconferencing. 25 Patient and provider interaction through telerehabilitation can be either synchronous (real-time rehabilitation) or asynchronous (delay between information being sent and received).…”
Section: Types Of Interventionmentioning
confidence: 99%
“…Randomized controlled trials delivering physical therapy care by telerehabilitation were included. The experimental group received telerehabilitation, which was considered as home-based exercises delivered through mobile applications, web-based instruments, exergames, 24 and videoconferencing. 25 Patient and provider interaction through telerehabilitation can be either synchronous (real-time rehabilitation) or asynchronous (delay between information being sent and received).…”
Section: Types Of Interventionmentioning
confidence: 99%
“…The field of healthcare technologies is vast and growing. It encompasses communication tools that allow remote consultations, 10,11 smart objects 12,13 and wearable devices [14][15][16] that can measure physical and physiological variables, technologies (including immersive and non-immersive virtual reality [VR] and augmented reality [AR]) that allow gamification of rehabilitation activities, [17][18][19] assistive and adaptive technologies, 20,21 and web-or mobile-based tools (including apps) that permit self-management and recording and sharing of information and patient-reported outcomes. 22,23 Some technologies are nascent and others are more established.…”
Section: Web-based Rehabilitation Compared To General Information For...mentioning
confidence: 99%
“…The use of a Microsoft Kinect in rehabilitation for conditions including stroke, neurorehabilitation and frozen shoulder is well published in the literature 8,14,21,30 . In a recent metaanalysis Steiner et al 36 concluded that there are limited applications designed for rehabilitation of the shoulder. They found that those available commercially failed to deliver programs tailored to the multiple phases of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%